Room temperature self-assembly and nonenzymatic electrochemical sensing performance of transition metal-embedded wheel-shaped tungstophosphates - Wen-Da Liu; Hao-Tian Zhu; Xue Zhang; Fang Su; Xiao-Jing Sang; Xiao-Lan Zhang; Lan-Cui Zhang (Polyoxometalates)
Under heat-free conditions, three wheel-shaped [P8W48O184]40− (P8W48)-based polyoxometalates (POMs) were controllably synthesized via the reaction of a hexavacant Dawson-type tungstophosphate, K12[H2P2W12O48]·24H2O (K-P2W12), with simple transition metal (TM) (TM = Mn, Co, and Ni) salts in room temperature aqueous solutions. The molecular formulas of the POMs were Na24[Mn8(H2O)32P8W48O184]·58H2O (1), K4Na16H4[Co8(H2O)32P8W48O184]·76H2O (2), and Na20H4[Ni8(H2O)32P8W48O184]·72H2O (3). It should be noted that eight TM ions introduced into each POM skeleton were connected in a P8W48 wheel. To the best of our knowledge, this is the first time that the self-assembly of 3d-TM-P8W48 with the internal coordination of all metals in an aqueous solution was achieved without heating. Compounds 1–3 were characterized by elemental, single-crystal X-ray diffraction, and other physical and spectral analyses, and their nonenzymatic electrochemical sensing performance for hydrogen peroxide (H2O2) was investigated by cyclic voltammetry. Compared with K28Li5[H7P8W48O184]·92H2O without 3d-TM and most reported POM electrode materials, the proposed 3d-TM-P8W48 POMs exhibited higher stability and better activity during H2O2 detection. Composite films formed using 1–3 and chitosan (CS) on a glassy carbon electrode exhibited a high sensitivity (1.21 μA∙mmol∙L−1), low detection limit (0.02 mmol∙L−1), and rapid response time (2 s) for H2O2 detection. The study findings show that the combination of CS and 1–3 provides an alternative to soluble TM-P8W48 compounds, which are not reusable in H2O2 detection systems.